Second Five Year Plan Progress Report for 1956-57 Himachal Pradesh Administration - Planning Commission (Planning Commission, 1956)
The present volume embodies a review of the progress for the first year i.e. 1956-57, of the Second hive Year Plan. Due to limitations of data, a comprehensive analysis of achievements has not been possible in certain cases. Nevertheless, it is hoped that the report will afford a compact picture of the progress of the Plan during the year 1956-57. The main reason for the delay in bringing out this review is that the requisite data could not be made readily available by some of the Departments concerned with the execution of the Plan.
Himachal Pradesh Administration